Hansen's Disease with Torpid Evolution. A Case Report - Graciela Caridad Cabrera Acea; Joan Bernárdez Ruíz; Maricela García de la Torre (Centro Provincial de Información de Ciencias Médicas. Cienfuegos, 2012)
We report the case of a female patient with cutaneous manifestations of leprosy, whose clinical presentation was atypical and of torpid evolution. From disease onset, the patient developed polymorphic skin lesions accompanied by sensory disturbances. The initial diagnosis was indeterminate leprosy. Multibacillary treatment was indicated. After two years of evolution, given the exacerbation of lesions and general symptoms worsening, biopsy was performed again, providing the following histological result: Hansen dimorphic, the result of the sputum smear being negative. In 2001, a nerve conduction study showed axomielynic damage in the sensory fibers of the right crural nerve. In 2004 the patient presented hives without stinging that left white stains when they disappeared. From that date until 2008 she continued to refer the disease. Multidisciplinary interconsultation was performed in coordination with the national team leader and she was assessed at the meeting of specialists in Havana City, where they initiated therapy with rifampicin, ofloxacin and minocycline, under which she remained for a year, with a satisfactory outcome.